Quick Wilt Disease of Pepper-11 : Techniques for Screening Pepper Varieties Against Quick Wilt Disease Caused by Phytophthora Palmivora(Butler) Butler - Vilasini T N (Department of Plant Pathology, College of Horticulture, 1982)
The present study on the quick wilt disease of pepper (Piper nigrum Lin.) was conducted at the College of Horticulture, Vellanikkara. The objective of this study is to find out a rapid and perfect technique to screen large number of Piper types (both open polinatede and hybrid seedlings) against Phytophthora palmivora (Sutler) Butler, the quick wilt (foot rot) organism of black pepper. P. palmivora is capable of producing phytotoxin in vitro. The leaves of P. nigrum assayed with the propagule-free dialysed culture filtrate of P. palmivora, produced necrotic symptoms typical of the natural infection. Five liquid media were tested for production of toxic metabolite by the pathogen. Out of this, Richards + yeast extract broth was found to be the best medium followed by potato dextrose broth which is on par with thiamine enriched synthetic liquid medium for Phytophthora. Seventeen p. nigrum types (open pollinated, hybrid and panniyur-1) were screened against P. palmivora. Three different plant parts namely, leaves (both detached and undetached), stem cuttings and roots were inoculated with viable pathogen and bio-assayed with propagule-free dialysed culture filtrate. The enoculation of the pathogen and administration of propagule-free dialysed culture filtrate on the leaves of potted pepper plants and detached leaves showed the same symptom expression as that of the natural infection of the pathogen. All the pepper types tested were found highly susceptible to leaf infection. Undetached leaves were found better to study the resistance of pepper plants to the disease, due to slow and steady development of symptom on inoculation with the pathogen. Stem cuttings of all the P. nigrum types were inoculated with zoospore suspension and bio-assayed with propagule-free dialysed culture filtrate. The lesion development in both cases were typio of the natural infection of the pathogen. All the pepper types tasted for the stem reaction showed no significant difference between the types, with respect to the symptom expression. The roots of cuttings were inoculated with zoospore suspension and assayed with propagule-free dialysed culture filtrates. In all the pepper types tested by both methods, the entire root system were found decayed within three days after the administration of culture filtrate and within five days on inoculation with zoospore suspension. All the seventeen P. nigrum types tested were found highly susceptible to root infection.